The Impact of Dual Health Care System Use for Obtaining Prescription Medications on Nonadherence in Veterans With Type 2 Diabetes. Issue 7 (July 2019) - Taber, David J.; Ward, Ralph; Axon, R. Neal; Walker, Rebekah J.; Egede, Leonard E.; Gebregziabher, Mulugeta
Background: Dual health system use may provide increased access to physicians, medications, and other health care resources but may also increase the complexity and coordination of medication regimens. Thus, it is important to elucidate the impact of dual use on medication adherence.Objective: The objective of this study was to evaluate the impact on medication adherence for veterans with dual health care system use (VA and Medicare) when obtaining prescription antihyperglycemic medications to treat diabetes.Methods: This was a longitudinal cohort study using VA and Medicare data from 2006 to 2010. Medication adherence was estimated by calculating annualized drug class-level proportion of days covered (PDC), where PDC >80% was considered adherent. Generalized linear models were used for estimations, accounting for correlation over time.Results: In total, 254 267 veterans with diabetes were included, with 71 057 (27.9%) defined as pharmacy system dual users. Mean age was 77.5 years, and nearly all had multiple comorbidities (mean count 10.2). During follow-up, 75% of VA-only users were deemed adherent to diabetes prescriptions, compared with 63% of dual users. In adjusted models, dual prescription benefit use from VA/Medicare was associated with 39% lower odds of medication adherence (odds ratio [OR] = 0.61; 95% CI = 0.60-0.61). Medication adherence significantly worsened with each additional diabetes medication (OR = 0.65; 95% CI = 0.64-0.65) and significantly decreased over time (OR = 0.95 per year; 95% CI = 0.95-0.96).Conclusion and Relevance: These data suggest that veterans utilizing VA and Medicare to obtain diabetes prescriptions are significantly less likely to be adherent.